Design of PID, IMC and IMC based PID Controller for Hydro Turbine Power System of Non-minimum Phase Dynamics - Bhuran, Supriya Y.; Jadhav, Sharad P. (Journal of Robotics and Control (JRC), 2024)
The primary objective of this paper is to design and assess the performance of conventional Proportional Integral Derivative (PID), Internal Model Controller (IMC), and IMCbased PID controllers tailored for Hydro Turbine Power Systems (HTPS) exhibiting Non-Minimum Phase (NMP) dynamics. The focus is on overcoming the limitations of existing approaches in handling such complex system dynamics. Existing literature underscores the difficulty of crafting controllers for such systems. The current study represents a sincere endeavour to design and evaluate the performance of conventional Proportional Integral and Derivative (PID), Internal Model Controller (IMC), and IMCbased PID controllers tailored for HTPS characterized by NMP behaviour. The design case study and simulations were conducted using MATLAB and Simulink. The closed-loop responses of HTPS with PID, IMC, and IMC-PID are presented, and the controller performances are scrutinized in both time and frequency domains. To validate the effectiveness of the controllers, performance indices such as Integrated Squared Error (ISE), Integrated Absolute Error (IAE), Integrated Time-weighted Absolute Error (ITAE), Integrated Time Squared Error (ITSE) are calculated, as well as control efforts are calculated using 2-norm and infinity-norms. These performance indices and control effort norms offer a comprehensive evaluation of the controllers’ performance in terms of minimizing error, handling system dynamics, and optimizing control effort across different time scales. Analysing these metrics aids in selecting and refining controllers for optimal performance in HTPS with NMP behaviour. Our findings illustrate that IMCbased PID controllers exhibit superior performance compared to conventional PID controllers in effectively handling the NonMinimum Phase (NMP) dynamics of Hydro Turbine Power Systems (HTPS). This superiority is substantiated by enhanced performance indices, including reductions in ISE, IAE, ITSE, and ITAE.